EVALUASI KEPATUHAN PENERBIT AL-QUR’AN TERHADAP MEKANISME PENERBITAN, PENTASHIHAN, DAN PEREDARAN MUSHAF AL-QUR’AN DI INDONESIA - Muchlis Muhammad Hanafi; Zaenal Arifin Madzkur; Ali Akbar; Mustopa Mustopa; Abdul Hakim; Imam Suseno; Heru Suparman (Lajnah Pentashihan Mushaf Al-Qur'an, 2021)
This article aims to evaluate of the extent to which publishers of the Qur’an obey the Regulation of the Minister of Religious Affairs Number 44 of 2016 in keeping the authenticity of the text of the Qur’an in Indonesia. Using an evaluation research approach, this research took place from September to November 2021. The research data was obtained through distributing questionnaires and interviews to the selected publishers who were randomly selected as research respondents. The results showed that the obedience of the publishers of the Qur’an was classified as “the Very Obedient”. However, in the field, new things were found that attracted attention in the implementation of the regulations concerning the publication, printing and circulation of the Qur’an. Something which appears is considered a new trend and has not been accommodated in the mechanism of rectification of the Qur’an yet. The results of this study recommend several things, among others are the need to add aspects of mushaf printing to the regulation of the Minister of Religious Affairs.